ANALYSIS OF THE MATERIALS OF ISLAMIC RELIGION EDUCATION THROUGH THEOLOGICAL APPROACHES: STUDY OF THE ISLAMIC RELIGIOUS EDUCATION AND CHARACTER TEXTBOOK FOR GRADE 1 OF ELEMENTARY SCHOOL - Sofiyandi, Muji Agus; Tobroni, Tobroni; Faridi, Faridi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
This research is qualitative research with a literature review approach by examining PAI content in PAI textbooks and Class 1 Elementary School Characters in a theological context. The objectives include: 1) carrying out theological categorization of the content of Islamic Religious Education in the textbook Islamic Religious Education and Character Class 1, 2) classifying the material in the book based on a theological approach, and 3) exploring its relevance. PAI content in the book is aimed at contemporary Islamic education. The primary data source for this research is the PAI and Character Class 1 Elementary School Textbook written by Nurzakun & Santoso (2021). The analysis technique used is content analysis. The findings of this research indicate that: 1) the content of PAI in the PAI and Character textbooks for Grade 1 Elementary School can be considered comprehensive and presented in simple language to facilitate students' understanding; 2) The contents of the book cover theological themes, with the main focus on theocentric themes; 3) Holistically, the PAI content in this book can be seen as relevant and significantly contributing in a theological context. This study contributes to a deeper understanding of PAI content about theological aspects, thereby increasing understanding in this academic domain. The implications of this research are: 1) Relevance of learning, 2) Development of character textbooks, 3) Development of professional teachers, 4) Curriculum development, 5) Increasing understanding of Islam, 6) Involvement of parents and the community in the implementation of education.